Validation of Malay-version incontinence quality of life (I-QOL) and incontinence praying ability (I-PA) among childbearing women attending Hospital Universiti Sains Malaysia - Ismail, Hanis (2016)
INTRODUCTION: The assessment of quality-of life and praying ability become crucial especially among women. However, there are no any validated instruments to assess those aspects in Malaysia population. Thus, the study will focused on validation of Malay-version Incontinence Quality of Life (I-QOL) and Incontinence Praying Ability (I-PA) among Muslim women under childbearing age. I-QOL was an established instrument that measure quality-of-life among UI patients and had been widely used by other countries while I-PA was new developed instrument that focus on praying ability among UI patients. This new developed instrument was made based on Malaysia population that majority among them were Muslim. OBJECTIVES: To determine the construct validity and reliability of I-QOL and I-PA model among Muslim women under childbearing age that attends particular clinics at HUSM by EFA and CFA as well as to assess the concurrent validity between both models. METHODS: Cross-sectional study was done in two phase of EFA and CFA. Thus, data collection was done two times. EFA was assessed by using statistical software of SPSS version 22. It was conducted by using Principal Axis Factoring (PAF) extraction method with promax rotation. While CFA was measured by using statistical software of Mplus version 7.3 and was conducted by using MLM estimation. RESULTS: All items of I-PA were remained in the model during the EFA phase and the measurement reliability by cronbach‟s alpha was 0.946. Assessment by CFA reported the final model of I-PA consist one factor and 10 item with 5 error covariance with value of CFI=0.971 and TLI=0.956. While, the measurement of I-QoL by CFA reported the final model consist one factor and 22 items with 12 error covariance with value of CFI=0.932 and TLI=0.920. CONCLUSION: I-QOL and I-PA were proven to be valid and reliable in Malay language among Muslim women under childbearing age and there were high correlation between both of them